Consequences of excessive pesticide use in corn cultivation (Zea mays L.) in the Callejón de Huaylas, 2018-2019 season. (Aporte Santiaguino, 2025)
This research was conducted in the maize-producing areas of the districts of Tinco, Carhuaz, Acopampa, and Marcará, in the province of Carhuaz, Callejón de Huaylas, Ancash, with the objective of determining the consequences of excessive pesticide use in maize cultivation. The methodology included direct interviews through semi-structured surveys and visits to farmers’ plots. A total of 63 farmers were interviewed, identifying Mathamidophos, Methomyl, Cypermethrin, and the herbicide Glyphosate as the most commonly used pesticides. These products are marketed under different trade names, which often causes confusion among farmers. The results show that 77.77% of farmers apply pesticides every eight days without using protective measures. Although there are no documented records of environmental contamination in the study area or in the Callejón de Huaylas, farmers reported cases of intoxication in both people and animals. In addition, an increase in pest populations was observed due to the mortality of natural controllers caused by repeated pesticide applications, ranging from 15 to 18 per five-month growing season. Finally, the increase in production costs is not determined by the farmer. All these problems negatively affect the quality of life of farmers and society.
Keywords: Pesticides; Maize; Callejon de Huaylas; Methamidophos; Methomyl; Cypermethrin